2020
DOI: 10.1038/s41598-020-79188-z
|View full text |Cite
|
Sign up to set email alerts
|

CO2 utilization as a soft oxidant for the synthesis of styrene from ethylbenzene over Co3O4 supported on magnesium aluminate spinel: role of spinel activation temperature

Abstract: Magnesium aluminate spinel (MgAl2O4) supported Co3O4 catalysts are synthesized and tested for the oxidative dehydrogenation (ODH) of ethylbenzene using CO2 as a soft oxidant. The effect of spinel calcination temperature on the catalytic performance has been systematically investigated. With an increase in the activation temperature from 600 to 900 °C, the active presence of a single-phase MgAl2O4 spinel is observed. A catalyst series consisting of MgAl2O4 spinel with varying Co loadings (10–20 wt%) were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…[ 34 ] The band at 585 cm −1 was attributed to stretching vibrations of M–O. [ 35 ] The results indicated that the main structure of organic ligand H 4 DHTP remains unchanged after the synthesis reaction and further confirmed the successful coordination of metal ions and ligand H 4 DHTP.…”
Section: Resultsmentioning
confidence: 97%
“…[ 34 ] The band at 585 cm −1 was attributed to stretching vibrations of M–O. [ 35 ] The results indicated that the main structure of organic ligand H 4 DHTP remains unchanged after the synthesis reaction and further confirmed the successful coordination of metal ions and ligand H 4 DHTP.…”
Section: Resultsmentioning
confidence: 97%
“…NH 3 -TPD was carried out to evaluate the strength of acid sites in the catalyst surface. We differentiate two zones associated with the acid strength, depending on the NH 3 temperatures desorption: moderate (200–400°C) and strong (400–800°C) ( Madduluri et al, 2020 ). The peak at a lower temperature, 256°C, is associated with reversible adsorption H-bonded ascribed to hydroxyl groups presence over the surface, considered as BrØnsted acid sites ( Song et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the present N-pincer Pd(II)-porphyrin catalyzed process is advantageous over the reported aryltrifluoroborate self-couplings. In view of global sustainability, the elimination/decrease of the application of volatile organics, the use of benign/naturemimicking catalysts, and conducting the chemical reactions at ambient conditions can make a significant contribution [74][75][76][77][78]. A comparison of reported self-coupling procedures of aryltrifluoroborates [39][40][41][42][43] is shown in Table 3 and evidences the clear merits of the present nature-mimicking method over the reported protocols using Pd NPs/Te-Dps [39], Au nanoclusters:poly(N-vinyl-2-pyrrolidine) [40], Pd(OAc)2-electrolysis [41], Cu(OAc)2-ultra sound [42], and Pd NPs@Al(OH)3 [43] which require organic solvent [41], base/additive [39][40][41][42][43], heating [39][40][41][42][43], long process time [39,40,42,43] or suffer from low biaryl yield with some aryltrifluoroborates [39][40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the present N-pincer Pd(II)-porphyrin catalyzed process is advantageous over the reported aryltrifluoroborate self-couplings. In view of global sustainability, the elimination/decrease of the application of volatile organics, the use of benign/nature-mimicking catalysts, and conducting the chemical reactions at ambient conditions can make a significant contribution [74][75][76][77][78].…”
Section: Resultsmentioning
confidence: 99%